2014
DOI: 10.3892/or.2014.3152
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of glutathione peroxidase 3 is associated with lymph node metastasis and prognosis in cervical cancer

Abstract: Abstract. Glutathione peroxidase 3 (GPX3) is a member of the glutathione peroxidase family of selenoproteins and is one of the key defensive enzymes against oxidative damages to host cells. Downregulation of GPX3 due to its promoter hypermethylation has been documented in several different types of cancer, indicating that GPX3 functions as a possible tumor suppressor. In the present study, we showed that GPX3 is also significantly downregulated in cervical cancer tissues compared to normal cervical tissues by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…Tumor suppressor function of GPX3 in vivo and in vitro has been identified in a number of tumors . Additionally, reduced expression of GPX3 caused by its promoter hypermethylation has been observed in various solid tumors . Simultaneously, our previous studies also have proved the epigenetic style of GPX3 in AML and chronic myeloid leukemia (CML), and further disclosed that hypermethylation of GPX3 promoter was a prognostically adverse indicator in AML .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Tumor suppressor function of GPX3 in vivo and in vitro has been identified in a number of tumors . Additionally, reduced expression of GPX3 caused by its promoter hypermethylation has been observed in various solid tumors . Simultaneously, our previous studies also have proved the epigenetic style of GPX3 in AML and chronic myeloid leukemia (CML), and further disclosed that hypermethylation of GPX3 promoter was a prognostically adverse indicator in AML .…”
Section: Introductionmentioning
confidence: 82%
“…have revealed that GPX3 plays a vital role in the competitiveness of leukemic stem cells (LSCs) and self‐renewal activity of HSCs . Recently, increasing studies have demonstrated the reduced expression of GPX3 and hypermethylation of GPX3 promoter in various types of malignancies . Furthermore, epigenetic mechanism regulating GPX3 expression was also identified in human cancer cells including esophageal squamous cell carcinoma (ESCC), cervical cancer (CC), gastric carcinoma (GC), and multiple myeloma (MM) .…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with prostate cancer with high GPx2 expression on the biopsy specimen had significantly lower prostate-specific antigen (PSA), recurrence-free survival, and OS than those without any GPx2 expression 69. Downregulation of GPx3 significantly correlated with poor prognosis in hepatocellular carcinoma,70 cervical cancer,71 and gallbladder cancer 72. GPx3 is considered to be a novel tumor suppressor, because hypermethylation of the GPx3 promoter was detected in tumor samples from patients with Barrett’s esophagus3537 as well as endometrial38 and prostate cancers,39 and downregulation of GPx3 was generally associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, methylation of the ESR1 promoter was related to higher tumor grading of patients with CC [32]. CpG promoter methylation could result in GPX3 (a possible tumor suppressor) downregulation in CC [33]. The methylation of APC1A promoter was also closely correlated with biological features in CC and could therefore be used to predict poor prognosis of CC [34].…”
Section: Discussionmentioning
confidence: 99%